2019
DOI: 10.1016/j.jcot.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 12 week prehabilitation program on pain and function for patients undergoing total knee arthroplasty: A prospective controlled study

Abstract: Background: The concept of preparing the body before a stressful event, such as surgery, has been termed "prehabilitation" (preoperative physiotherapy and exercise programs). Prehabilitation programs for people awaiting total knee arthroplasty (TKA) have positive effects on patients health status and may also lead to better postoperative outcomes. Aim: The purpose of this study was to examine effect of a prehabilitation program on knee pain, functional ability among patients with knee osteoarthritis after TKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…A shorter hospital stay was also reported by Matassi et al (9.1 ± 2.1 vs. 9.9 ± 2.3 days) [14] and in the study by Williamson et al for those patients that underwent home-based [14] or supervised (6.5 vs. 7.7 days) [13] strengthening programs. The major difference registered, though not statistically significant, occurred in the study by Aytekin et al, where the average length of stay was longer in the intervention group (5.5 ± 2 vs. 7.9 ± 2.3 days; p > 0.05) [20]. A prospective case series by Twiggs et al [7] showed a poor positive correlation (rho = −0.114, p > 0.05) between preoperative step count and hospital length of stay.…”
Section: Clinical Outcome Datamentioning
confidence: 75%
See 3 more Smart Citations
“…A shorter hospital stay was also reported by Matassi et al (9.1 ± 2.1 vs. 9.9 ± 2.3 days) [14] and in the study by Williamson et al for those patients that underwent home-based [14] or supervised (6.5 vs. 7.7 days) [13] strengthening programs. The major difference registered, though not statistically significant, occurred in the study by Aytekin et al, where the average length of stay was longer in the intervention group (5.5 ± 2 vs. 7.9 ± 2.3 days; p > 0.05) [20]. A prospective case series by Twiggs et al [7] showed a poor positive correlation (rho = −0.114, p > 0.05) between preoperative step count and hospital length of stay.…”
Section: Clinical Outcome Datamentioning
confidence: 75%
“…Contrary to these results, the progressive strength training program advocated in the study by VanLeeuwen et al yielded comparable functional results between groups in terms of 6MWT and chair stand [12]. Similarly, in the paper by Aytekin et al [20], KOOS and VAS were comparable between intervention group (home-based strengthening and stretching exercises) and controls. In the case series by Twiggs et al [7], a significant correlation was found between preoperative step count and KOOS (activity of daily living subscore) immediately before surgery (rho = 0.282, p < 0.05).…”
Section: Clinical Outcome Datamentioning
confidence: 79%
See 2 more Smart Citations
“…Holmgren et al found in individuals with subacrominal impingement that a strengthening program to the rotator cuff and scapular stabilizers improved pain and function, thus reducing the need for subacrominal decompression surgery 53) . In a 12-week total knee arthroplasty (TKA) prehab program, 19.4% of the participants elected to cancel surgery due to improved pain 54) .…”
Section: Discussionmentioning
confidence: 99%